2017
DOI: 10.5007/1980-0037.2017v19n3p261
|View full text |Cite
|
Sign up to set email alerts
|

Validação da Subjective Vitality Scale e estudo da vitalidade nos idosos em função da sua atividade física

Abstract: -The main aim of the study was to validate the Portuguese version of the Subjective Vitality Scale -SVS for the Portuguese elderly population through of confirmatory factorial analysis. The existence of differences in the perception of subjective vitality among sufficiently active and insufficiently active older adults was also analyzed. A total of 309 Portuguese elderly (242 females, 67 males) aged 60-90 years (M = 68.59, SD = 6.60) participated in this study. Of the total sample, 256 are sufficiently active,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
2
0
4
Order By: Relevance
“…A study by Moksnes et al [22] showed that high satisfaction with life is associated with a series of positive personal, behavioral, psychological, and social results, but low satisfaction with life is associated with higher levels of stress, psychologic disorders, and behavioral problems. Previous research done with adult populations reinforces this significant inverse relationship between satisfaction with life and depression [23][24][25].…”
Section: Satisfaction With Life: Potential Mediator Between Coping Mechanisms and Depressive Symptomsmentioning
confidence: 70%
“…A study by Moksnes et al [22] showed that high satisfaction with life is associated with a series of positive personal, behavioral, psychological, and social results, but low satisfaction with life is associated with higher levels of stress, psychologic disorders, and behavioral problems. Previous research done with adult populations reinforces this significant inverse relationship between satisfaction with life and depression [23][24][25].…”
Section: Satisfaction With Life: Potential Mediator Between Coping Mechanisms and Depressive Symptomsmentioning
confidence: 70%
“…Subjetive Vitality Scale (SVS: Ryan & Frederick, 1997), validada para população sénior portuguesa (Couto et al, 2017), permite avaliar a vitalidade subjetiva nos idosos portugueses. A SVS é constituída por seis itens, aos quais se responde numa escala tipo Likert, com sete possibilidades de resposta.…”
Section: Instrumentosunclassified
“…Desta forma, a prática regular de atividade física ou exercício físico tem um efeito positivo na manutenção da capacidade física do sujeito ao longo do tempo (Hertzog, Kramer, Wilson, & Lindenberger, 2008), e está positivamente relacionada com a vitalidade subjetiva nesta população, uma vez que maiores índices de atividade física estão associados a maiores valores de vitalidade e, por outro lado, índices mais baixos de exercicio físico, estão associados a menor perceção de vitalidade (Couto et al, 2017;Neto et al, 2012;Withall et al, 2014).…”
Section: Introductionunclassified
“…A 6-item version was suggested by Bostic et al (2000) who used structural equation modeling techniques to prove the model fit. A 6-item version was also recommended by Castillo et al (2017) and Couto et al (2017) in Spanish and Portuguese, respectively. All 6-item versions removed the only negatively worded item (I don't feel very energetic).…”
Section: Introductionmentioning
confidence: 99%